TRADISI PENULISAN DALAM PROSES TRANSFORMASI HADIS - Mustofa 'Umar (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2013)
Abstract: The Orientation of present paper to be researching and discussing on hadith transformation through writing tradition. In the early of this process, dominant paradigm in classical hadith scholars in hadith transformation based on oral tradition without writing tradition until second half century. This not without strong argument, there is hadith statement on prohibiting of hadith writing. This phenomena has impact on authenticity the materials of hadith after their codification. In historically context, writing of hadith happened in middle of conflict moslem in political and school of thought. The alleged wholesale fabrication of hadith in seen as result of the activities of group of scholars and foremost as result of interpretation from point of view of praxis. Abstrak: Orientasi dari paper sekarang ini untuk meneliti dan mendiskusikan tentang transformasi hadis sepanjang tradisi penulisan. Dalam proses awal dari proses ini, paradigma yang dominan di kalangan ulama hadis dalam transformasi hadis berdasarkan pada tradisi lisan tanpa tradisi tulis hingga paroh abad kedua. Ini bukanlah tanpa argumen yang kuat, ada pernyataan hadis mengenai larangan penulisan hadis. Fenomena berpengaruh pada otensitas material-material hadis setelah kodifikasi mereka. Dalam konteks sejarah, penulisan hadis terjadi di tengah konflik kaum Muslim di bidang politik dan mazhab pemikiran. Terjadi pemalsuan hadis besar-besaran yang dilihat sebagai hasil dari aktivitas-aktivitas kelompok ulama dan terkemuka sebagai hasil dari interpretasi berdasarkan sudut pandang praksis. Kata-kata Kunci: hadis, sunnah, al-Quran, Kutubi, ahl al-ra’y, ahl al-ḥadīṡ.